Exploring the development of front office instructional module from the experts’ opinions - Quah, Wei Boon; Sulaiman, Tajularipin; Razali, Fazilah (International Journal of Evaluation and Research in Education (IJERE), 2025)
In the world of hospitality, the front office plays a crucial role as it is the first point of contact for guests entering a hotel. This makes front office operation (FOO) a vital subject in hospitality education programs, especially at community colleges. While there is a growing body of research on FOO, there's a lack of instructional modules designed specifically for community college students. To address this gap, a study was conducted to understand the need for developing a FOO module based on expert opinions. Using the analyze, design, develop, implement, and evaluate (ADDIE) framework, data from three experts were analyzed. Educators cited issues such as limited practice time, communication skill hesitancy, and struggles with term comprehension and pronunciation. Meanwhile, students encountered obstacles like inadequate practical equipment, unsupportive learning environments, and overwhelming syllabi. Nonetheless, educators acknowledged the potential of a FOO instructional module to enhance student learning experiences. This study emphasizes the significance of crafting a tailored module for community college students, paving the way for advancements in hospitality education.